2020
DOI: 10.3390/molecules25051178
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Chromium-Iron Oxidation Mixture Cermet-Based Solar Selective Absorbing Coatings

Abstract: The solar selective absorber coating (SSAC) are at the core of the efficient solar-thermal system. In this paper, for the first time, the Chromium-iron oxidation mixture cermet was successfully prepared on the surface of ultra-pure ferritic stainless steel by chemical coloring as SSAC. The coating surface has an optical trap structure, and the chromium-iron oxidation mixture cermet is used as an absorption layer to realize solar-thermal conversion. The solar absorptance (AM1.5) of the coating reached 93.66, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It can be found in Figure that the reflectance spectra changed little after heating in the air at 600 °C for 144 h; the α̅ solar and ε̅ IR were almost constant at 0.817 and 0.098, respectively. These results indicated that SSAs prepared by high-temperature in situ oxidation had excellent thermal stability at 600 °C, which can be attributed to the Cr 2 O 3 with outstanding thermal stability. …”
Section: Resultsmentioning
confidence: 84%
“…It can be found in Figure that the reflectance spectra changed little after heating in the air at 600 °C for 144 h; the α̅ solar and ε̅ IR were almost constant at 0.817 and 0.098, respectively. These results indicated that SSAs prepared by high-temperature in situ oxidation had excellent thermal stability at 600 °C, which can be attributed to the Cr 2 O 3 with outstanding thermal stability. …”
Section: Resultsmentioning
confidence: 84%
“…These coatings are designed to have the maximum possible absorbance and minimum reflectance of the incident solar radiation while maintaining a minimum emittance value. Many materials were designed to closely meeting these specifications [3][4][5][6]. Among the promising materials investigated nickelpigmented aluminum oxide [7], nickel-aluminum (NiAl) alloy embedded into black paint [8], CrNxOy/SiO2 on Cu(Si) substrate deposited by DC reactive magnetron sputtering method [9], black chrome or carbon-coating [10] have been investigated showing advantageous solarthermal conversion characteristics for flat plate collector systems.…”
Section: Introductionmentioning
confidence: 99%